The Petrography and geochemistry of iron-bearing units from Mingo’o area (Ntem complex, southern Cameroon) - Edjo-Minko, Rodrigue; Isaac Bertrand Mbowou , GBAMBIE; Daama , Isaac; Nguihdama, Dagwai; Mienlam Essi , Mike-Franck (International Journal of Advanced Geosciences, 2024)
The banded iron formation (BIF) of the Mingo’o region is located on the northern edge of the Congo Craton. They constitute a significant component of the southern Cameroonian Archean to Paleoproterozoic. Petrographic description indicates that the most characteristic facies of the Mingo'o BIFs are quartz-magnetite BIFs (QMB), which are mostly composed of magnetite and quartz. Geochemistry analyses show that the major elements of this BIF are very simple, with SiO2 and Fe2O3 representing 95.25 wt. % of the bulk rock on average. The low concentrations of Al2O3, TiO2, and HFSE reveal that these chemical sediments are detritus-free. According to Paerson's major element correlation matrix, there is a slight contribution of detrital material to chemical sediment, as confirmed by the strong positive correlation (r = 0.72) of Al and Ti, also by the binary diagrams Al vs. Σ(Y + Nb + Zr) with a weak positive correlation (r2 = 0.31) and Al vs. ΣREE with a zero correlation (r2 = 0.08), indicating that the detrital input was insignificant. The transition metals Zn, Cr, Sr, and V are among the trace elements with low enrichments. This suggests the direction of the volcanogenic hydrothermal input in chemical precipitates. The mean ∑REE concentration of the studied BIF is 26.74 ppm, with a range of 8.82 to 36.74 ppm. Pure chemical sediments are comparable to that. The shale-normalized patterns display minor positive europium anomalies, a sharp decrease in heavy REE, and enrichment in light REE. These geochemical characteristics suggest that the hydrothermal activity in the deep ocean, coupled with seawater, was the source of the Fe and Si. Low-temperature hydrothermal solutions play a key role in the studied BIF, as shown by the absence of a notable positive Eu anomaly. Ce anomalies are seen in the chrondrite-normalized REE patterns, which are characterized by LREE-enriched (mean LaCN/YbCN = 5.28) and HREE depletion (mean TbCN/YbCN = 1.04) patterns. This may indicate that the BIF within the Mingo’o region was formed in place of the basin towards redoxcline, alternating at different times and under various influences from the influx of seawater that has been oxidized.